A Critical Evaluation of Intervention Studies for Reducing Sexism and a Suggestion for a Classification - Nihan Selin Soylu Konak; İbrahim Mert Teközel (Psikoloji Çalışmaları)
Gender stereotypes and sexism has been a topic of discussion in politics and social psychology since the 1960s. The relationships between sexism and various social-psychological variables, as well as the effects of sexism and gender stereotypes on life satisfaction and accessibility of educational opportunities, have been examined. Therefore, previous research on sexism-reduction intervention has not reached a consensus. The major goal of this research is to review intervention studies and the current literature on the effects of sexism, as well as draw attention to the theoretical and methodological limitations of intervention studies and suggest a new classification model for future studies. According to this classification model, intervention studies addressing sexism can be classified into four basic dimensions: (1) intervention to the process of perceiving a stimulus containing sex information; (2) intervention to (implicitly or explicitly) the process of binding sex information to traits; (3) intervention to (explicit, subtle or implicit) sexist attitudes; and (4) intervention to sexist behavior. The essential aims of this model are to reduce the conceptual challenges and discrepancy between the findings and minimize the low comparability of such findings in the intervention studies. Considering various dimensions categorically and the transactions between the dimensions suggested in this model can contribute to the cumulative progress of relevant literature by providing comparable standards for results from different intervention studies. However, this model can facilitate an understanding of not only contradictory patterns of different intervention methods on various dimensions (e.g., reducing sexism on one dimension and increasing on another dimension) but also the complex relationships between sexist attitudes and behaviors. Lastly, the suggested fourdimension classification model was discussed within the scope of sexism theories and empirical intervention studies; focusing on sexism.